2021
DOI: 10.1038/s41419-021-03463-8
|View full text |Cite
|
Sign up to set email alerts
|

p53 induces ARTS to promote mitochondrial apoptosis

Abstract: Apoptosis related protein in TGF-β signaling pathway (ARTS) was originally discovered in cells undergoing apoptosis in response to TGF-β, but ARTS also acts downstream of many other apoptotic stimuli. ARTS induces apoptosis by antagonizing the anti-apoptotic proteins XIAP and Bcl-2. Here we identified the pro-apoptotic Sept4/ARTS gene as a p53-responsive target gene. Ectopic p53 and a variety of p53-inducing agents increased both mRNA and protein levels of ARTS, whereas ablation of p53 reduced ARTS expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Following nutlin-3 treatment, p53 levels increase rapidly, and p53 is either translocated to the nucleus, where it regulates transcription, or localized to mitochondria ( Figure 1 ). It has been hypothesized that the indirect effects of MDM2 inhibitors on the nuclear transcription machinery might contribute to their cytotoxicity by inducing the transcription of pro-apoptotic genes, such as NFRSF10B/TRAIL-R2 ( 47 , 48 ), PUMA ( 48 51 ), BAX ( 51 54 ) and the apoptosis-related protein in TGF-β signaling pathway ARTS ( 55 ). However, several studies have shown that inhibition of p53 transcriptional activity (by other agents) significantly increases MDM2 inhibitors-mediated cytotoxicity ( 44 , 56 58 ).…”
Section: Action Of Mdm2 Inhibitors On Nuclear Gene Transcription and ...mentioning
confidence: 99%
“…Following nutlin-3 treatment, p53 levels increase rapidly, and p53 is either translocated to the nucleus, where it regulates transcription, or localized to mitochondria ( Figure 1 ). It has been hypothesized that the indirect effects of MDM2 inhibitors on the nuclear transcription machinery might contribute to their cytotoxicity by inducing the transcription of pro-apoptotic genes, such as NFRSF10B/TRAIL-R2 ( 47 , 48 ), PUMA ( 48 51 ), BAX ( 51 54 ) and the apoptosis-related protein in TGF-β signaling pathway ARTS ( 55 ). However, several studies have shown that inhibition of p53 transcriptional activity (by other agents) significantly increases MDM2 inhibitors-mediated cytotoxicity ( 44 , 56 58 ).…”
Section: Action Of Mdm2 Inhibitors On Nuclear Gene Transcription and ...mentioning
confidence: 99%
“…Inducers of p53 can increase the expression of ARTS, and the blocking of p53 can diminish the expression of ARTS under various stress conditions. These findings indicate that ARTS and p53 act synergistically on apoptosis involving mitochondria [71].…”
Section: Discussionmentioning
confidence: 72%
“…Another mode of action is the non‐transcription‐dependent mitochondrial mechanism, namely, direct translocation of P53 out of the nucleus, inducing the release of cytochrome C in the mitochondrial membrane space, activating the caspase cascade, and finally executing apoptosis by cleaved‐caspase‐3 to promote the mitochondrial apoptosis pathway. P53‐mediated apoptosis is an important way for P53 to act as a tumor suppressor gene 39‐41 . Therefore, P53, P21, caspase‐3, cleaved‐caspase‐3, which are key proteins regulating the cell cycle and apoptosis process, were selected to verify the role of the rapeseed peptide in inhibiting the proliferation process of HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%